Evaluasi Pengukuran Taraf Kebisingan dan Getaran di Kapal untuk Menjamin Lingkungan Kerja yang Aman dan Nyaman bagi Awak Kapal - Ximenes, Yonifia (PT Yupin Felicitas Utama, 2025)
Evaluation of noise and vibration level measurements on ships is carried out to ensure a safe and comfortable working environment for the ship's crew. These measurements are carried out at various critical locations on the ship, such as the engine room, bridge, and crew living area, using noise and vibration measuring instruments according to ISO 6954:2000 standards and SOLAS 2020 regulations. The test results show that the noise and vibration levels are within the maximum permissible limits, which are 6 to 8 mm/s and in accordance with the established standards, so that the working environment conditions are considered safe and meet health requirements. In addition, working time arrangements based on noise levels are also carried out to protect workers' health from the dangers of excessive noise exposure. This study emphasizes the importance of shipboard work environment management to prevent health risks and maintain crew comfort while sailing, as well as providing recommendations for improvements to improve safety and health in the ship's environment.